Risk characteristics of covered bonds: Monitoring beyond ratings - Magdalena Grothe; Jana Zeyer (European Central Bank (ECB), 2020)
This paper proposes a set of indicators relevant for the risk characteristics of covered bonds, as based on granular publicly available transparency data. The indicators capture various aspects of cash flow risks related to the issuer, the cover pool and the payment structure. They offer unified risk metrics for the European covered bond universe, which ensures comparability across covered bonds issued by different issuers and rated by different credit rating agencies. The availability of granular risk indicators adds to the overall transparency of the market in the context of risk monitoring.
Keywords: G12; G24; G21; C30; 330; covered bonds; risk monitoring; risk indicators; covered bond transparency data; credit ratings